2002
DOI: 10.1074/jbc.m104587200
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Mediates Shock Wave Induction of ERK-dependent Osteogenic Transcription Factor (CBFA1) and Mesenchymal Cell Differentiation toward Osteoprogenitors

Abstract: ؊ by superoxide dismutase and inhibition of ERK activation by PD98059 decreased specific osteogenic transcription factor, core binding factor A1 activation, and decreased osteocalcin expression. Taken together, we showed that ESW-induced O 2 ؊ production followed by tyrosine kinase-mediated ERK activation and core binding factor A1 activation resulted in osteogenic cell growth and maturation. Thus, an appropriate modulation of redox reaction by ESW may have some positive effect on the bone regeneration.Oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
127
1
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 64 publications
9
127
1
6
Order By: Relevance
“…We recently have found that bone morphogenetic proteins (BMPs) are actively involved in ESW-promoted healing of segmental defects [44]. Osteogenic transcription factor (CbfallRunx2) and Indian hedgehog (Ihh) are further candidates to mediate chondrogenic and osteogenic differentiation of mesenchymal stem cells after ESW treatment [43].…”
Section: Discussionmentioning
confidence: 99%
“…We recently have found that bone morphogenetic proteins (BMPs) are actively involved in ESW-promoted healing of segmental defects [44]. Osteogenic transcription factor (CbfallRunx2) and Indian hedgehog (Ihh) are further candidates to mediate chondrogenic and osteogenic differentiation of mesenchymal stem cells after ESW treatment [43].…”
Section: Discussionmentioning
confidence: 99%
“…[31] ERK can stimulate the osteoblast-related gene expression by extracellular matrix-integrin receptor interaction, BMP-2, growth factors, and mechanostressing. [31][32][33][34] Xiao et al [35] demonstrated that stimulation of MAPK enhances the expression of osteocalcin, whereas the ERK-specific inhibitor (PD98059) inhibits expression. Our data show that PD98059 significantly inhibits AOPP-induced calcium deposition and OPN expression, indicating that AOPP can promote osteoblast differentiation and calcification of HASMCs via the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity of the cell lysate was measured using p-nitrophenylphosphate (pNPP), as described previously (15). ALP activity was expressed as nmol p-nitrophenol produced per min/mg of total protein.…”
Section: Methodsmentioning
confidence: 99%